(untitled) (The Research of Medical Science Review, 2024)
The Assessment and Treatment Strategies utilized by Clinical Psychologists when working with Suicidal Clients were the subject of this phenomenological investigation. In-depth and semi-structured interviews with ten clinical psychologists were conducted, and the data were afterward iteratively analyzed using theoretical coding based on the phenomenological approach. The primary theme that emerged from the data was the "Clinical approach of Clinical Psychologists treating suicidal clients," it was supported by three auxiliary themes, including diagnostic techniques, therapeutic assessments, and therapeutic approaches. According to the study, clinical psychologists determine if a client is now contemplating suicide or has in the recent past to gauge their level of suicidality. To understand their customers' mental health, they use psychological diagnostic instruments and various treatment approaches, such as psychotherapy, for clients contemplating suicide, hospitalization, or patient care is required. This study serves as a foundation for future research by offering insight into the Assessment and Treatment Strategies employed by Clinical Psychologists.